Cemetery of Iron Bones: The bare bones of the junkyards (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
Junkyards are places of memory and oblivion which are full of objects and materials that once have lost their purpose. It is through scenic investigation that they can become places of renewal. It is precisely from the mining carried out in these cemeteries of iron bones that we can find some of the clues for understanding the Phenotypic Structures that form a Scenographic Composition. Here we will weave our reflections from memories of my childhood and a brief look at a theatrical play in which I worked as a scenographer, makeup and hair designer.
Keywords: scenographic composition; phenotypic structures; junkyard